Experimental and computational analyses reveal that environmental restrictions shape HIV-1 spread in 3D cultures - Imle, Andrea; Kumberger, Peter; Schnellbaecher, Nikolas D.; Fehr, Jana; Carrillo-Bustamante, Paola; Ales, Janez; Schmidt, Philip; Ritter, Christian; Godinez, William J.; Mueller, Barbara; Rohr, Karl; Hamprecht, Fred A.; et al. (Nature Communications, 2019)
Pathogens face varying microenvironments in vivo, but suitable experimental systems and analysis tools to dissect how three-dimensional (3D) tissue environments impact pathogen spread are lacking. Here we develop an Integrative method to Study Pathogen spread by Experiment and Computation within Tissue-like 3D cultures (INSPECT-3D), combining quantification of pathogen replication with imaging to study single-cell and cell population dynamics. We apply INSPECT-3D to analyze HIV-1 spread between primary human CD4 T-lymphocytes using collagen as tissue-like 3D-scaffold. Measurements of virus replication, infectivity, diffusion, cellular motility and interactions are combined by mathematical analyses into an integrated spatial infection model to estimate parameters governing HIV-1 spread. This reveals that environmental restrictions limit infection by cell-free virions but promote cell-associated HIV-1 transmission. Experimental validation identifies cell motility and density as essential determinants of efficacy and mode of HIV-1 spread in 3D. INSPECT-3D represents an adaptable method for quantitative time-resolved analyses of 3D pathogen spread.
CRIS-Team Scopus Importer:2022-12-14